Neovagina creation methods and their potential impact on subsequent uterus transplantation: a review. (13th August 2019) - Kölle, A; Taran, F‐A; Rall, K; Schöller, D; Wallwiener, D; Brucker, SY
Abstract : Congenital uterovaginal aplasia commonly occurs in Mayer–Rokitansky–Küster–Hauser syndrome. Various methods of neovagina creation exist, including nonsurgical self‐dilation, surgical dilation, and surgical procedures involving skin or intestinal transplants. Subsequent uterus transplantation is necessary to enable pregnancy. We review the main characteristics, advantages, and disadvantages of established neovagina creation methods and discuss their suitability regarding subsequent uterus transplantation. Suitability criteria include sufficient vaginal length, absence of previous major intra‐abdominal surgery, a natural vaginal axis, and a natural vaginal epithelium. In conclusion, Vecchietti‐based laparoscopically assisted neovagina creation provides ideal functional conditions for uterus transplantation. Nonsurgical self‐dilation and Wharton–Sheares–George vaginoplasty may also be suitable. Tweetable abstract: This review discusses the main advantages and disadvantages of neovagina creation methods with regard to subsequent uterus transplantation. Tweetable abstract: This review discusses the main advantages and disadvantages of neovagina creation methods with regard to subsequent uterus transplantation.